PENGARUH MODEL PEMBELAJARAN KOLABORATIF (COLLABORATIF LEARNING) TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 108/1 SEI RUMBAI TAHUN AJARAN 2025/2026 - Astria, Mira; Fauzi, KMA; Andayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of science and natural sciences at SD Negeri 108/1 Sei Rumbai due to the dominance of teacher-centered learning and minimal interaction between students. The purpose of this study is to describe the development and influence of the Collaborative Learning Model on the learning outcomes of science and natural sciences in fifth grade students in the 2025/2026 academic year. This study uses a Descriptive Qualitative method with a Classroom Action Research (CAR) design. The subjects of the study were 12 fifth grade students (6 boys, 6 girls). The study was conducted in three meetings, through the systematic stages of Engagement, Exploration, Transformation, Presentation, and Reflection. Data collection was carried out through Student Worksheets (LKPD), analysis of learning outcomes (formative/summative), and in-depth observation. The success criterion was set if 90% of students achieved the KKM 80. The results showed that the implementation of the Collaborative Learning Model successfully improved students' science and natural science learning outcomes. In addition, this model significantly increased student interaction, activeness, and participation in the learning process. Qualitatively, the Collaborative Learning Model has a positive influence on the learning process and outcomes of fifth-grade students. Teachers are advised to optimize their role as facilitators in managing group dynamics so that all students actively contribute.